Evaluation of Laundry Process Applied to Bed Linen in Selected Hospitals of Karachi - Afreen, Mahlaqa; Iqbal, Nimra (Nurture, 2009)
Hospital laundry is associated with infection control. Adequate linen supply and general health and safety of patients are interrelated. The purpose of this study was to find out the appropriateness of laundry processes applied to bed linen, specifically bed sheets in selected hospitals of Karachi. The sample consisted of 12 hospitals of Karachi. The information was gathered using a questionnaire assisted interview of relevant mangers and the evaluations are based on comparison of the respondent’s reports with the recommendations of the laundry standards of International Standard Organization (ISO). The findings revealed that most of the hospitals do not follow ISO’s laundry standards but apply their self-made standards. When these standards were compared with ISO’s laundry standards they were found to be insufficient for example regarding the washing temperature and the use of disinfectants. The reasons to use the own standards instead of those of ISO’s were the lack of space, the lack of funds and the lack of the awareness of ISO’s standards. It is recommended that government should take measures to make the application of ISO’s laundry standards compulsory for bed sheets in the hospitals of Karachi.